O PATRÓN DESIGUAL DE CRECEMENTO EUROPEO: UNHA ANÁLISE SEMIPARAMÉTRICA A NIVEL REXIONAL - DANIEL RODRÍGUEZ GONZÁLEZ; XAVIER VENCE DEZA (Revista Galega de Economía, 2013)
The aim of this paper is to analyze the relationship between inequality and the equivalent dispo- sable income available at a regional level and to contrast the type of relationship between two variables in the developed world in the context of a standard neoclassical growth model. In this paper we will estimate a panel data model using the method of OLS fixed effects, and also analyze the possible existence of spatial autocorrelation in the model and the need for implementation of spatial models. A novel contribution is estimated by a semiparametric analysis, which allows conditional no Relational function. Semiparametric analysis, unlike the nonparametric analysis, allows the introduction of other variables by a linear function defined as the initial inequality, population density, employment in various sectors (industry mix), transfers, etc. This application of the semiparametric analysis is a relevant contribution to the study, since it is still a novel technique for the study of inequality.